PENGEMBANGAN BUKU TEKS PERENCANAAN PEMENTASAN DRAMA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONSIA UNIVERSITAS BATURAJA - Contessa, Emilia; Huriyah, Shofiyatul (LPPM STKIP PGRI Bandar Lampung, 2020)
Abstrac: Knowledge and abilities about drama are very important for students in the context of learning Indonesian. This ability is one of the abilities that students must have. By having knowledge related to drama theory, it makes it easier for students to apply it to stage art in the form of drama performances. The problems in this research are (1) how is the description of the teaching material needs for the Drama Performance Planning Study Program of Indonesian Language and Literature Education, Faculty of Teacher Training and Education, Baturaja University? Indonesian Language and Literature, Faculty of Teacher Training and Education, University of Baturaja ?, (3) what is the potential effect of developed textbooks on the Dramatic Performance course in the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Baturaja University ?. This study aims to (1) describe the need for teaching materials for Drama Performance Planning in the form of textbooks in the Indonesian Language and Literature Study Program Staging course, Faculty of Teacher Training and Education, Baturaja University, (2) produce textbooks according to the needs of the Language Education Study Program. and Indonesian Literature, Faculty of Teacher Training and Education, University of Baturaja, (3) to describe the potential effects of the Drama Performance Planning textbook on learning outcomes. The data collection techniques used were pretest and posttest. To see the feasibility of the textbook, the researcher conducted a validation test on four experts, namely, validation of content / material feasibility, presentation feasibility validation, linguistic validation, and grammatical validation. The data on the textbook trial obtained through a multiple choice test of 50 questions showed that the average score of students at the pretest showed the lowest score of 33 and the highest score of 67 with an average of 53.20. After using the developed textbook and posttesting, the students' scores got an increase, namely the lowest score of 67 and the highest score of 87 with an average of 71.70 The increase in pragmatic ability was also seen from the difference between the average test of 18.5. Thus the researcher concludes that the developed textbooks have a potential influence in improving students' learning abilities.